The Political Economy of Corporate Tax Harmonization: Why Do European Politicians (Dis)like Minimum Tax Rates? - Steffen Osterloh; Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Setting minimum tax rates is a well discussed way of mitigating pressure from tax competition. This paper investigates which motives shape the support for a minimum corporate tax among politicians. We make use of a unique data base: a survey among members of the European parliament. Our results confirm that the politicians' ideology as well as individual characteristics such as educational background exert a major in uence. Moreover, several predictions regarding national interests are derived from various standard tax competition models. These hypotheses are partly supported by the data; in particular, different national preferences for social equality shape the support. A comparison with survey results from the German Bundestag reveals that German politicians on the national level do not show different preferences towards tax rate harmonization.
Keywords: H25; H87; D78; 330; company taxation; tax harmonization; political economy; European Parliament; Körperschaftsteuer; Unternehmensbesteuerung; EU-Steuerrecht; Steuerharmonisierung; Public Choice; EU-Staaten; Deutschland